2019
DOI: 10.1186/s12876-019-1143-5
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenetic approach to the treatment of functional disorders of the gastrointestinal tract and their intersection: results of the Russian observation retrospective program COMFORT

Abstract: BackgroundThe aim of this study was to investigate the efficacy and safety of the novel complex drug, consisting of released-active form of antibodies to S-100 protein, tumor necrosis factor-α and histamine, (Kolofort) under outpatient conditions in patients with functional dyspepsia (FD), irritable bowel syndrome (IBS), and FD-IBS overlap.MethodsThe subjects of the observational noninterventional retrospective program were the data of 14,362 outpatient records of patients with diagnosed FD, IBS, and/or overla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
0
6
0
12
Order By: Relevance
“…Similar to our results, as in most observational studies, FGID symptoms improved during the follow-up period. 51 , 52 This may be related to treatment in any form (medication or education, etc) or reassurance when visiting a hospital for FGID symptoms. However, as has already been found, FGID symptoms are often associated with other factors, especially psychological factors such as anxiety and depression, 53 , 54 so that symptoms may not improve or rather worsen during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, as in most observational studies, FGID symptoms improved during the follow-up period. 51 , 52 This may be related to treatment in any form (medication or education, etc) or reassurance when visiting a hospital for FGID symptoms. However, as has already been found, FGID symptoms are often associated with other factors, especially psychological factors such as anxiety and depression, 53 , 54 so that symptoms may not improve or rather worsen during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…To date, more and more data on their effectiveness appear. In particular, it has been shown that high dilutions of antibodies can be used to treat various diseases [24][25][26][27][28]. High dilutions exert a modifying effect on the properties of the starting material [29][30][31][32][33], despite the colossal difference in the quantities of mixed substances (of the original substance and its high dilution).…”
Section: Introductionmentioning
confidence: 99%
“…• Пациентам с СРК рекомендуется назначение комбинированного лекарственного препарата, содержащего антитела к мозгоспецифическому белку S-100, антитела к человеческому фактору некроза опухоли альфа аффинно очищенные, для уменьшения боли в животе, нормализации частоты и консистенции стула [70][71][72].…”
Section: уровень убедительности рекомендаций -B (уровень достоверности доказательств -2)unclassified
“…Комментарии: Данный препарат оказывает спазмолитическое, противовоспалительное и анксиолитическое действие. Эффективность препарата была доказана в рандомизированных плацебо-контролируемых исследованиях [70][71][72]. Курс лечения 1-3 месяца; при необходимости курс лечения можно продлить до 6 месяцев и/или повторить через 1-2 месяца.…”
Section: уровень убедительности рекомендаций -C (уровень достоверности доказательств -3)unclassified
See 1 more Smart Citation